The participation of family farming production in the Brazilian basic food basket items - da Silva, Bruce Wellington Amorin [UNESP]; Borda, Diogo Erik Saénz [UNESP]; Lourenzani, Wagner Luiz [UNESP]; Palácio, Vinícius [UNESP]; Oliveira, Kátia Cilene Schnoor [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Family farming is an important social organization, it is the focus of many studies and public policies. It provides food for society and plays a role in regional development, and food and nutritional security. Family farms represent 90% of the agricultural establishments worldwide and 77% in Brazil. From this, it is important to understand the degree of importance of family farmers in food production. Therefore, the objective of this research is to analyze the participation of family farming in the production of Brazilian basic food basket items. Not all items were directly used because some of them were industrialized, such as sugar, and then some substitutes were chosen, like sugarcane. This is possibly the main limitation of this research. The results indicate there is varied participation of family farming production among the items, ranging from 1.93% (sugarcane) to 84.55% (coffee beans). The literature indicates different percentages of participation of family farming in agricultural production, depending on the definition of family farming and the crops considered for analysis. In this research, the results indicate a general participation of 17.21% for the Brazilian basic food basket items. As exploratory research, the results are considered satisfactory and can contribute to the formulation of public and private policies concerning food production and supply.
Keywords: Basic food basket; Family farming; Food production; Food security